Phenotypic and Allelic Distribution of the ABO and Rhesus Blood Groups among students at Hawassa University, Ethiopia - Mihret A. Hailu; Wendawek A. Mengesha; Zelalem G. Tolesa (East African Journal of Biophysical and Computational Sciences)
A prior information on the distribution of ABO and Rh groups is important for management of blood bank and transfusion, genetic counseling, anthropological studies, to study the association of blood groups and diet; to investigate the association between blood and diseases. This study aimed to determine the frequency of ABO and Rh bloods and investigate gene diversity at both loci among students in Ethiopia.  A descriptive cross-sectional survey was employed involving randomly selected two thousand thirty nine (2039) university students (1054 males and 985 females) with an age range of 18–29 years. Blood groups were determined based on agglutination reaction. The most common blood group was found to be O (42.47%), followed by A (27.86%), B (21.87%), and AB (7.80 %). The frequency of Rh+ and Rh- were 90.88% and 9.12 %, respectively. The combined blood types showed O+, A+, B+ and AB+ were: 38.60 %, 25.20%, 20.10%  and 7.00%, respectively. A slightly different distribution pattern of ABO blood group was observed among females from Amhara region (O> B> A>AB). The distribution of ABO phenotypes from Addis Ababa and Amhara did not differ significantly from those expected under the Hardy Weinberg Equilibrium. A high level of gene diversity was observed for both loci. In general, the O blood type is most frequent and followed by A, B and AB. A similar pattern of distribution of the ABO and Rh blood groups was found in male and female study subjects. The present study will generate baseline data that could be used in blood bank management and transfusion, genetic counseling, population genetic and anthropological studies, and for disease management.